Ibn Rushd's Intellectual Representation in Al-Massir: The Dialectic of Reason-Revelation (1126-1198) - Dhimas Sugian (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the representation of Ibn Rushd in Youssef Chahine’s Al-Massir (1997) through the dialectical framework of reason and revelation. As a central figure in Islamic philosophy, Ibn Rushd is portrayed as a symbol of rationalism confronting theological conservatism and intellectual repression. Using a qualitative descriptive method and film semiotic analysis, this research analyzes how cinematic narratives construct the relationship between al- ‘aql (reason) and al-naql (revelation) within visual discourse. The findings reveal that Al-Massir functions not only as a historical reconstruction of twelfth-century Andalusia but also as a contemporary critique of anti-intellectualism, censorship, and dogmatism. The film ultimately reaffirms Ibn Rushd’s epistemological thesis that philosophy and religion are fundamentally harmonious and mutually reinforcing.